(untitled) - Williams, Trevor I. (New York, 1987)
Readers looking for information on technologies—past and present—need look no further. The History of Invention takes readers on a fascinating journey that begins with the most primitive tools and weapons and ends with the latest technological advances in communications, genetics, engineering, construction, medicine, transportation, architecture, agriculture, and space exploration...
Keywords: Technology,Lịch sử khoa học công nghệ; History